Ileostomy Prolapse in Children with Intestinal Dysmotility - Eric A. Sparks; Cristine S. Velazco; Brenna S. Fullerton; Jeremy G. Fisher; Faraz A. Khan; Amber M. Hall; Tom Jaksic; Leonel Rodriguez; Biren P. Modi (Gastroenterology Research and Practice)
Background. A relationship between intestinal motility and ileostomy prolapse has been suggested but not demonstrated objectively. Aims. This study evaluated the association between ileostomy prolapse and intestinal dysmotility in children. Methods. IRB-approved retrospective review of 163 patients with ileostomies (1998–2014) at a single institution. Patients were categorized as having clinical dysmotility as a primary diagnosis (n=33), clinically suspected dysmotility based on underlying diagnosis (n=60), or intestinal dysmotility unlikely (n=70) at the time of ileostomy present. Intestinal manometry was categorized as normal (n=13) or abnormal (n=10). Primary outcome was pathologic stoma prolapse. Multivariate analysis using a logistic regression model and log-rank test to compare stoma prolapse rates over time between motility groups were used. Results. Clinical diagnosis of dysmotility (p≤0.001) and manometric findings of dysmotility (p=0.024) were independently associated with stoma prolapse. Clinical dysmotility correlated with manometric findings (κ=0.53). Prolapse occurred in 42% of patients with dysmotility, 34% of patients with suspected dysmotility, and 24% of patients with normal motility. One-year prolapse-free stoma “survival” was 45% for dysmotility, 72% for suspected dysmotility, and 85% for intestinal dysmotility unlikely groups (p=0.006). Conclusions. Children with intestinal dysmotility are at great risk for stoma prolapse. Intestinal manometry could help identify these patients preoperatively.